THE EFFECT OF THE USE OF MASK ON THE INCIDENCE OF ACNE VULGARIS IN STUDENTS OF MEDICAL FACULTY DIPONEGORO UNIVERSITY - Devy Kurniawati; Dhega Anindita Wibowo; Puguh Riyanto; Widyawati Widyawati (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Acne vulgaris (AV) is an inflammatory condition of pilosebaceous follicles that is commonly experienced in adolescents and young adults. The pathogenesis of AV is multifactorial, such as caused by inflammation and external factors of acne exposome, which have an impact on the pathogenesis of acne in the use of masks.Objective: To determine the effect of using a mask and the number of acne vulgaris on students of the Faculty of Medicine, Diponegoro University.Methods: This research is an observational type with a cross sectional design. The research subjects were 58 students of the Faculty of Medicine, Diponegoro University with an age range of 19-23 years who used masks. The data obtained are primary data from the questionnaire. The analytical test used is bivariate chi square analysis.Results: This study showed that there was no significant effect between the type of mask and the incidence of acne vulgaris p 0.610 (p>0.05), the duration of the use of masks and the incidence of acne vulgaris p 0.200 (p>0.05), and the frequency of using masks with the incidence of acne vulgaris p 0.689. (p>0.05)Conclusion: There is no effect between the use of masks and the incidence of acne vulgaris.